Analysis of Improvement Strategies for the Ngudikan Kiri Irrigation Network Using the Analytical Hierarchy Process (Case Study: Ngudikan Kiri Irrigation System, Nganjuk Regency): Analisis Strategi Perbaikan Jaringan Irigasi Ngudikan Kiri Menggunakan Metode Analytical Hierarchy Process (Studi Kasus: Jaringan Irigasi Ngudikan Kiri Kabupaten Nganjuk) - Stevania, Egha; Bambang Sujatmiko; Dayat Indri Yuliastuti (PUBLIKASI RISET ORIENTASI TEKNIK SIPIL (PROTEKSI), 2025)
Efficient irrigation is essential for supporting agricultural productivity in Nganjuk Regency. The Ngudikan Kiri irrigation network, covering 645 hectares, was selected as the research object due to its suboptimal performance, which affects water distribution to farmers. This study aims to evaluate the network’s performance using the KP-01 (2013) guidelines and to formulate improvement strategies through the Analytical Hierarchy Process (AHP). Data were collected through field surveys, documentation, and interviews, and analyzed using a descriptive quantitative approach. The results provide priority recommendations for improvement strategies that align with actual field conditions. The results of the Water Balance analysis show that the highest water deficit during the rice planting season reached 7.58 m³/second in May I, while the maximum deficit during the secondary crop planting season was 1.56 m³/second in November I. AHP analysis revealed that the social support criterion has the highest weight of 0.23, with the main priority on channel rehabilitation (0.24), followed by scheduled irrigation (0.23) and measured water gates (0.20). This study emphasizes the need for improvements in irrigation management through infrastructure enhancement and more efficient water distribution regulation so that the irrigation system functions optimally and supports sustainable agricultural productivity.